Efficacy of Three Varietal Toxins of Bacillus thuringiensis Against Ailanthus Defoliator, Atteva fabriciella Swed. (Lepidoptera: Yponomeutidae) - Joshi, K. C.; Roychoudhury, N.; Sambath, S.; Humane, S.; Pandey, D. K. (Indian Forester, 1996)
Effectiveness of three varietal toxins of Bacillus thuringiensis viz. var. dendrolimus endotoxin, var. thuringiensis and its exotoxin and var .kurslaki endotoxin. Were evaluated in the laboratory against the last instar larvae of Atteua fabriciella Swed. By spraying on larvae and food plant, Alianthus excelsa Roxb. Results revealed that the spraying of B.t. on host plant was more effective in killing larvae than on the target pest, irrespective of toxines. Among the tested toxins, var. dendrolimus endotoxin proved to be highly effective and appeared to be best, both for larval and leaf treatment @ 2.0 and 1.5% respectively.